Photocatalytic oxidation of tyrosine using colloidal CdS particles under visible light irradiation - Pratigya Rizal; Devendra P. S. Negi (Scientific Reports)
Abstract The enzyme-catalyzed oxidation of tyrosine in living organisms leads to the formation of dopachrome which is a key intermediate in the melanogenesis pathway. Therefore, the present manuscript which describes the photocatalytic oxidation of tyrosine to dopachrome is significant. To the best of our knowledge, this is the first report on the use of semiconductor particles for the formation of dopachrome from tyrosine. In the present work, colloidal CdS particles were synthesized and characterized by X-ray diffraction (XRD) measurements and transmission electron microscopy (TEM). The irradiation of the reaction mixture containing 1 mM tyrosine and colloidal CdS particles in the presence of visible light resulted in an increase in the absorption in ultraviolet and visible region of the electronic spectrum. It suggested the formation of the products of the oxidation of tyrosine. Dityrosine and dopachrome were identified as the oxidation products of tyrosine based on the liquid chromatography-mass spectrometry (LC-MS) analysis. The probable reaction mechanisms were proposed for the formation of both the photoproducts.